FORMULASI SPRAY GEL MINYAK DAUN NILAM (Pogostemon calbin Benth) DENGAN VARIASI KOSENTRASI KARBOPOL DAN HPMC - Julia Susanti; Rosina Sitohang; Lina Br Tarigan, Frida; Yusfarida Laila Zhohrawati, Rosma (Universitas Sari Mutiara Indonesia, 2021)
Patchouli leaf oil spray gel formulation has been carried out, patchouli oil is one of the burns treatment. The purpose of this study was to determine whether the formation of a spray gel formulation of patchouli leaf oil with variance of the combination of carbopol 940 and HMPC 0.1%, 0.2%, 0.3% into a spray gel preparation and whether patchouli leaf oil can be used as a spray gel meets the requirements. quality of safety, this research is an experimental study which is carried out by testing organoleptic, homogeneity, viscosity, pH, spraying pattern, adhesive dispersion, stability, and irritation. The results of the spray gel preparations of carbopol 940 concentration variance and HPMC for organoleptic testing there was a cloudy white color change in the Cycling test, while the homogeneity test for all preparations was homogeneous, the viscosity test of the preparation showed that the 0.3% concentration did not meet the requirements, There was no change in the pH test on the preparations, namely neutral pH, tested for spraying patterns and the adhesion met the requirements of the 0.1% and 0.2% formulas. For the stability of the centrifugation there was no separation in the spray gel and for the irritation test there was no allergy in the respondent.